Houston chef's table : extraordinary recipes from the Bayou City's iconic restaurants - Meyer, Arthur L. (Lyons Press, 2012)
"Houston is the dining out capital of Texas, with a food scene that reflects the city itself--talented, entrepreneurial, diverse, and quite modern. Barbeque and Tex-Mex are certainly present, but do not define the dining experience. Modern American cuisine brought into focus by Mark Cox of Mark's American Cuisine and fine-dining Italian style served by award-winning Tony's both set the stage for a dining experience independent of Texas' reputation for big steaks and enchiladas. And numerous establishments court the palate for Thai, Indian, Caribbean, Brazilian, and Turkish foods. Houston Chef's Table is the first cookbook to gather Houston's best chefs and restaurants under one cover. Including a signature "at home" recipe from seventy iconic dining establishments, the book is a celebration of the city's diverse cultural influences. Full-color photos throughout highlight fabulous dishes, famous chefs, and Houston landmarks"--